2008
DOI: 10.1016/j.neulet.2007.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Protective properties afforded by pioglitazone against intrastriatal LPS in Sprague–Dawley rats

Abstract: We created an inflammation-induced Parkinson's disease model, where microglia activation leads to oxidative stress, mitochondrial dysfunction, and dopaminergic neurodegeneration in the substantia nigra. Pioglitazone, an agonist of peroxisome proliferator activated receptor-gamma (PPAR-γ), can prevent these deficits and protect dopaminergic neurons. To continue exploring the effects of pioglitazone in this model we focused on the expression of PPAR-γ, uncoupling protein 2 (UCP2), and mitoNEET. We report that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 30 publications
1
43
0
1
Order By: Relevance
“…Similarly, in animal models of ischemia, stroke, hypertension, stress, and Parkinson's disease, which are also characterized as pro-inflammatory conditions, PPAR-γ agonists provide significant neuroprotection [100], [101], [102], [103], [104], [105], [106], [107], [108], [109], [110], [111], [112]. In AD animal models also, PPAR-γ agonists appear to reduce baseline inflammatory levels [24], [26], [113], [114].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in animal models of ischemia, stroke, hypertension, stress, and Parkinson's disease, which are also characterized as pro-inflammatory conditions, PPAR-γ agonists provide significant neuroprotection [100], [101], [102], [103], [104], [105], [106], [107], [108], [109], [110], [111], [112]. In AD animal models also, PPAR-γ agonists appear to reduce baseline inflammatory levels [24], [26], [113], [114].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is suggested by the findings that: 1) in models of CNS injury, pioglitazone reduced mitochondrial dysfunction [36;37;75;93] and promoted glucose metabolism in astrocytes [19;66]; 2) pioglitazone reduced Aβ-induced astrocyte activation in the hippocampus [34]; 3) PPARγ is expressed in cortical astrocytes [17;58]; 4) astrocytes in the anterior cingulate cortex facilitate pain sensitization and inhibition [11;27;38;92]. This provides for the possibility that systemic pioglitazone administration produces anti-hyperalgesia through cortical, in addition to spinal, astrocytic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been postulated that activation of PPAR receptors accentuates mitochondrial biogenesis through stimulation of peroxisome proliferator-activated receptor gamma coactivator-1 family of proteins, which positively regulate mitochondrial functions and metabolism (Mootha et al 2003;Houten and Auwerx 2004). In a recent study, it has been suggested that Pioglitazone decreases the expression of mitochondrial protein mitoNEET, which therefore protects against mitochondrial impairment observed in AD (Feinstein et al 2005;Hunter et al 2008).…”
Section: Mitochondria Biogenesis and Energy Utilizationmentioning
confidence: 99%